2021
DOI: 10.1038/s41598-021-93214-8
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of 40 blood biomarkers of one-carbon metabolism, vitamin status, inflammation, and renal and endothelial function among cancer-free older adults

Abstract: Imbalances of blood biomarkers are associated with disease, and biomarkers may also vary non-pathologically across population groups. We described variation in concentrations of biomarkers of one-carbon metabolism, vitamin status, inflammation including tryptophan metabolism, and endothelial and renal function among cancer-free older adults. We analyzed 5167 cancer-free controls aged 40–80 years from 20 cohorts in the Lung Cancer Cohort Consortium (LC3). Centralized biochemical analyses of 40 biomarkers in pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 44 publications
(57 reference statements)
2
9
0
Order By: Relevance
“…In the present study we observed higher fasting serum concentrations of methionine, sarcosine and betaine in men when compared to women, which is partly in line with observations in a larger study in cancer-free older adults (42) . The higher fasting serum concentrations of trimethyllysine and 3-methylhistidine observed in our male participants may be a consequence of the larger muscle mass in men, since both methylated amino acids are found in muscle proteins (40) .…”
Section: Discussionsupporting
confidence: 92%
“…In the present study we observed higher fasting serum concentrations of methionine, sarcosine and betaine in men when compared to women, which is partly in line with observations in a larger study in cancer-free older adults (42) . The higher fasting serum concentrations of trimethyllysine and 3-methylhistidine observed in our male participants may be a consequence of the larger muscle mass in men, since both methylated amino acids are found in muscle proteins (40) .…”
Section: Discussionsupporting
confidence: 92%
“…A sedentary lifestyle will therefore unquestionably affect kynurenine metabolization (Alme et al, 2021). Previous work showing that most KYN metabolites correlate with BMI (Zahed et al, 2021) indicates that lifestyle influences tryptophan metabolism also at the level of food intake. The amount and type of alimentation strongly define both the essential amino acid's bioavailability and its metabolization.…”
Section: Living the Trycat Lifestylementioning
confidence: 99%
“…According to Zahed et al ( Zahed et al, 2021 ), most TRYCAT remain relatively unaffected by smoking, which only appears to decrease QUIN, AA, and 3-HAA ( Zahed et al, 2021 ). This may however be consequent to unassessed gender bias as Naz et al (2019) demonstrate KYN and KA (but not TRP) levels to be lower in male smokers vs. non-smokers but remain unaffected in female smokers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We are currently establishing a legal and technical infrastructure that will allow investigators outside of the LC3 consortium to request permission to remotely access and analyze the data in a secure computing environment. Available data will include the variables listed in Table 4 , the metabolomics biomarkers measured in the first project of the LC3, 36 and eventually the proteomics biomarkers following the publication of the validation phase of the project.…”
Section: Introductionmentioning
confidence: 99%